2006
DOI: 10.1111/j.1346-8138.2006.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome and sister chromatid exchange studies in Behcet's patients

Abstract: Behcet's disease is a chronic multisystemic disease of unknown pathogenesis characterized by four major symptoms: oral aphthous ulcers, skin lesions, ocular symptoms and genital ulcerations. The disease is spread throughout the world, but it is most frequent in Turkey, Japan, Korea and China. Although HLA-Bw51 has been found to predominate in Behcet's cases, the genetic etiology has not yet been clarified. In this study, we investigated the chromosomal abnormalities and sister chromatid exchange rates in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Behcet's disease has been shown to be associated with genotoxicity as measured by cytogenetic and oxidative DNA damage assays. For example, elevation in sister chromatid exchange (SCE) in BD lymphocytes has been shown by several reports (Ikbal et al 2006;Karaman et al 2009;Oztas et al 2006;Sonmez et al 1998). The increase in the SCE rate was evident in patients with active and inactive episodes (Karaman et al 2009) and in patients typed positive or negative for HLA-B51allele (Ikbal et al 2006).…”
Section: Introductionmentioning
confidence: 91%
“…Behcet's disease has been shown to be associated with genotoxicity as measured by cytogenetic and oxidative DNA damage assays. For example, elevation in sister chromatid exchange (SCE) in BD lymphocytes has been shown by several reports (Ikbal et al 2006;Karaman et al 2009;Oztas et al 2006;Sonmez et al 1998). The increase in the SCE rate was evident in patients with active and inactive episodes (Karaman et al 2009) and in patients typed positive or negative for HLA-B51allele (Ikbal et al 2006).…”
Section: Introductionmentioning
confidence: 91%
“…A higher incidence of sister chromatid exchange (SCE) can be associated with CIN, as is seen in some cancers and congenital syndromes [12][13][14][15][16]. Therefore, SCE has been used as a sensitive indicator of spontaneous CIN [12,[17][18][19][20]. Previous research has reported high SCE incidences in patients with Bloom syndrome, Werner syndrome, and various types of neoplasia [12,13,20].…”
Section: Introductionmentioning
confidence: 99%
“…Various physical and chemical agents and some idiopathic disorders have an increasing effect on frequencies of SCE. [12][13][14][15][16][17][18] The micronucleus (MN) frequency has also been used to determine genotoxicity on the human genome. The MN frequency is considered a direct indicator of numerical and structural chromosome damage.…”
mentioning
confidence: 99%